Analisis Perkembangan Kemampuan Sosial Emosional Anak Usia 4-6 Tahun di Tkn Nazaret Were : Analysis of the Development of Social and Emotional Skills of Children Aged 4-6 Years at Nazaret Were Kindergarten - Meo, Vinsensia; Marsianus Meka; Efrida Ita (Universitas Ngudi Waluyo, 2024)
This study aims to analyze the social emotional development activities of children aged 4-6 years at TKN Nazaret Were. This research was conducted at TKN Nazaret Were, Golewa District, Ngada Regency which was carried out within one month. The subjects in this study were 3 class teachers, 10 children and 10 parents of students. The results showed that the development of the child's social-emotional aspects did not develop according to the child's age level. This is caused by parenting patterns that are not in accordance with the needs of children, the level of health and nutrition of children who have not been fulfilled and learning methods that tend to be passive. Therefore a good understanding is needed in applying parenting patterns and applying learning methods. Various learning methods that can stimulate children's social emotional growth are exemplary, conversing, and telling stories. In applying the method, learning media should be used that support the method so that the goals of child development can be achieved optimally. ABSTRAK Penelitian ini bertujuan untuk menganalisis aktivitas perkembangan sosial emosional anak usia 4-6 tahun di TKN Nazaret Were. Penelitian ini dilakukan di TKN Nazaret Were Kecamatan Golewa Kabupaten Ngada yang dilaksanakan dalam waktu satu bulan. Adapun subyek dalam penelitian ini yaitu guru kelas sebanyak 3 orang, 10 orang anak serta 10 orangtua peserta didik. Hasil penelitian menunjukan bahwa perkembangan aspek sosial emosional anak tidak berkembang sesuai dengan tingkat usia anak. Hal ini disebapkan oleh pola pengasuhan yang tidak sesuai dengan kebutuhan anak, tingkat Kesehatan serta gizi anak yang belum tercukupi serta metode pembelajaran yang cendrung pasif. Oleh sebab itu diperlukan pemahaman yang baik dalam menerapkan pola pengasuhan serta penerapan metode pembelajaran. Berbagai metode pembelajaran yang dapat merangsang pertumbuhan social emosional anak yaitu keteladanan, bercakap-cakap, dan bercerita. Pada penerapan metode sebaiknya digunakan media pembelajaran yang menunjang metode tersebut sehingga tujuan perkembangan anak dapat dicapai secra optimal.